The Ventilation Duct Design in Temporary Ventilation System During Tunnelling Construction - Fauzana Amirah Binti Shaiful Rizam; Muhammad Shazwan Salimin; Muhamad Faiz Abd Latif (Progress in Engineering Application and Technology, 2022)
In tunnel construction, a lot of dust and gases were produced from excavation activities. It is essential to have a temporary ventilation system to provide fresh air for workers inside the tunnel during construction. Current technology used a ventilation duct that is connected to an axial fan to blow fresh air from outside the tunnel inside of the tunnel. The bigger size of the ventilation duct contributed to scratching the duct and taking a lot of space along the tunnel. Other works such as locomotive movement may be limited due to the bigger size of the ventilation duct. Therefore, in this paper studied on how to reduce ventilation duct sizing for Western Tunnelling Package (WTP) in Australia. In this study, I used the Reynolds Number method to identify how much to reduce for better ventilation duct to supply enough air inside the tunnel. For future ideas, I also give a suggestion to put a fan in the middle of the ventilation duct to pump more air for a better airflow inside the ventilation duct.